PENGEMBANGAN PULAU RUPAT SEBAGAI WISATA BUDAYA BERBASIS BUDAYA MELAYU DI RIAU - Bima Maulana Putra; Suroyo, Suroyo (LPPM Universitas Terbuka, 2022)
Development is basically from and for all people, it must involve and be recognized at all levels ofsociety in order to achieve the intended development goals. The usage of the Rupat Island center asa historical tour in Bengkalis regency is an example of eco-education, in which cultural heritage itempreservation is linked to educational renewal. This is a qualitative research project that usesparticipant observation and in-depth interviews. The findings suggest that regional growth on RupatIsland can be accomplished by leveraging a variety of factors, including districts, suburbs, landmarks,nodes, and paths that require government authorization in the Malacca area. If access to touristlocations is made easier, the development of Rupat Island as a cultural tourism destination has a lotof potential and appeal for regional cultural tourism destinations.